HALAL TOURISM IN LOMBOK ISLAND: POTENTIALS, CHALLENGES, AND THE ROLE OF ISLAMIC EDUCATION - Fitriani, Mohamad Iwan; Naamy, Nazar (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
Although Lombok of West Nusa Tenggara has gained good international reputation for its halal tourism (2015-2018), tourism in the region is not without obstacles. The Sasak-Lombok community, for instance, still refuses the concept of halal tourism because it is likely to cause harm to conventional tourism. This article will examine potentials, challenges, and the role of Islamic education in halal tourism in Lombok. It uses a descriptive-qualitative approach, where data collection is obtained from focus group discussions, in-depth interviews, document analysis, and media reporting. Meanwhile, data validity testing is done with triangulation technique. After a profound analysis, this research found that: (1) the potentials for halal tourism in Lombok are made of its natural beauty, cultural distinctiveness, and tradition of the local community predominated by Muslims; (2) the challenges of halal tourism in Lombok include two things: a) conceptual challenges that deal with the absence of terms representing the desires of all parties, and b) practical challenges that deal with economic, environmental, social, and cultural matters; (3) Islamic education?as a value, activity, or institution?plays an important role in disseminating representative concepts for halal tourism acceptable to all parties, i.e. the local community, tourism actors, and government. This acceptance is one of the keys to the successful development of halal tourism in Lombok.